The Challenges and Prospects of ICT Utilisation in Counter Terrorism Efforts in a Transitional Democracy: The Case of Nigeria - Nte, Ngboawaji Daniel; Okinono, Otega; Isa, Awal; Amadedon, Debi; Oba, Tovie Bodise-Ere (Faculty of Law Universitas Negeri Semarang, 2023)
The global quest to fight terror worldwide cannot be over emphasised as extremists and non -state actors continue to ravage the ungoverned spaces opening up around the globe. Consequently this work is an evaluation of the use of ICT in counter terrorism efforts in Nigeria as a fledgling democracy. The study reviewed the challenges and prospects of the application of ICT to counter terror in a country where Boko Haram, ISWAP, and other militant groups have continue to challenge the legitimacy and territorial integrity of the Nigerian state. The work used the mixed method –comprising qualitative and quantitative analytical efforts and found out that for the Nigerian State to make sustainable impacts in her counter terrorism efforts ICT should be the pivot. In the same vein, the study advocated adequate training and sustainable Information Technology policy and culture that will encourage the development of substantial capacity to drive an ICT-driven counter terrorism in a world full of rapidly mutating terrorism.